2014
DOI: 10.1007/s12034-014-0073-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substrate on structural, morphological and optical properties of ZnO films grown by SILAR method

Abstract: ZnO films were obtained by successive ionic layer adsorption and reaction (SILAR) method from four different substrates: glass microslides, corning glass, quartz and silicon with and without oxide layer. For films deposition, a precursor solution of ZnSO4 was used, complexed with ammonium hydroxide. Prior to the film deposition, wettability of the substrates was analysed using a CCD camera. It was found that the Si without the oxide layer substrate shows hydrophobic behaviour, which makes the films less adhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Zinc oxide (ZnO) has gained a particular interest among other metal semiconductor oxides due to its outstanding and unique properties including its direct-wide band gap (3.37 eV), large binding energy (60 eV) at room temperature [1] , low-cost material [2] , nontoxic and chemically-inert material [3] . ZnO was employed in various fields like light-emitting diodes, UV-photo-detectors, solar cells, gas sensors, pH sensors, and nano-lasers [4] , [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Zinc oxide (ZnO) has gained a particular interest among other metal semiconductor oxides due to its outstanding and unique properties including its direct-wide band gap (3.37 eV), large binding energy (60 eV) at room temperature [1] , low-cost material [2] , nontoxic and chemically-inert material [3] . ZnO was employed in various fields like light-emitting diodes, UV-photo-detectors, solar cells, gas sensors, pH sensors, and nano-lasers [4] , [5] .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, sensor with mixed oxides Zn 2 SnO 4 and ZnSnO 3 ) exhibits un increase of response to reach the maximum value of 20.8% at the 1000 pm concentration of LPG gas for them. Fig.22 shows the response time as a function of gas concentration, it can be seen that the time diminish by increased gas concentration [26,27]. And it is higher for pure oxide and fewer for mixed oxides.…”
Section: Finally Inmentioning
confidence: 97%
“…It can be observed that sensors of ZnO and SnO 2 show relatively low response at the same operating temperature in the range from (10 -1000) ppm, with the maximum response of 71.5% and 80.61% for ZnO and SnO 2 , at 1000 ppm respectively. Will sensor with mixed oxides (Zn 2 SnO 4 , ZnSnO 3 ) exhibits un increase of response to reach the maximum value of 89.57% at the 1000 pm concentration of H 2 S gas for them [25,26]. Fig.18 shows the Response time as a function of gas concentration, it can be seen that the time diminish by increased gas concentration.…”
Section: Finally Inmentioning
confidence: 99%
“…ZnO is also low-cost, nontoxic and chemically-inert material. Additionally, ZnO has hexagonal structure [5]. It has been widely utilized in optoelectronic applications such as sensors, LCDs, UV laser diodes, solar cells and plasma displays [6].…”
Section: Introductionmentioning
confidence: 99%